Fourth hankel determinant for a subclass of starlike functions - Norlyda Mohamed,; Atira Azira Zakri,; Nur Naqibah Ali,; Nurfatin Fadhilah Zain Karimy,; Aminah Abdul Malek, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Let B be the class of normalized starlike functions f z  which are analytic on an open unit disc E z z   { : 1} and satisfy Re ' '' 0   f z zf z       for some 0 1    and 0 1    . In this paper, we will obtain a sharp bound of the fourth Hankel determinant, H4 1 .